PENDIDIKAN KEWIRAUSAHAAN SEBAGAI PEMEDIASI PENGARUH SELF EFFICACY TERHADAP ENTREPRENEUR INTENTION MAHASISWA PROGRAM STUDI MANAJEMEN UNWIKU PURWOKERTO - Ratna Pujiastuti; Heru Cahyo (FEB UNWIKU PURWOKERTO, 2020)
This study to analyze the effect of Self efficacy on entrepreneurial education, to test the significance of the effect of self efficacy on entrepreneurial intention, the effect of entrepreneurship education on entrepreneurial intention, and entrepreneurial education in mediating the effect of self efficacy on entrepreneurial intention students in Management Study programs.The number of samples 75 respondens ,and the sampling technique using random sampling method. The analysis method uses regression and Sobel test. Based on the results of a simple regression analysis of the first model, the value of t-test of self-efficacy variables towards entrepreneurial intention (4,080) is greater than the value of ttable (1,993). From the results of a simple regression analysis of the second model, the value of the t test of the Self Efficacy variable towards entrepreneurship education (5,420) is greater than the value of the table (1,993). From the results of multiple regression analysis, the t test value of the entrepreneurship education variable (5.508) is also greater than the value of the table (1.993). Furthermore, based on the results of the mediation variable test with the Sobel test obtained t sobel value of (3.244) is greater than the value of the table (1.993). Thus, the first, second, third and fourth hypotheses in this study were accepted. Based on the results of data analysis, it can be concluded that Self Efficacy has a significant effect on entrepreneurship education. Self efficacy has a significant effect on entrepreneurial intention. Entrepreneurship Education has a significant effect on entrepreneurial intention. Entrepreneurship Education mediates the effect of Self Efficacy on entrepreneurial intention on Management students. Referring to these conclusions, it can be implied that as an effort to continuously improve entrepreneurial intentions, the management study program needs to implement appropriate policies related to entrepreneurship education. The ways that can be done include by continuing to improve the material provided in accordance with the contents of the syllabus, making entrepreneurial practice interesting so that this course pleases students.